Evolutionary functional morphology of the proboscis and feeding apparatus of hawk moths (Sphingidae: Lepidoptera). (16th September 2022) - Reinwald, Caroline; Bauder, Julia A.‐S.; Karolyi, Florian; Neulinger, Michael; Jaros, Sarah; Metscher, Brian; Krenn, Harald W.
Abstract: The morphology of the proboscis and associated feeding organs was studied in several nectar‐feeding hawk moths, as well as a specialized honey‐feeder and two supposedly nonfeeding species. The proboscis lengths ranged from a few millimeters to more than 200 mm. Despite the variation in proboscis length and feeding strategy, the principle external and internal composition of the galeae, the stipes pump, and the suction pump were similar across all species. The morphology of the smooth and slender proboscis is highly conserved among all lineages of nectar‐feeding Sphingidae. Remarkably, they share a typical arrangement of the sensilla at the tip. The number and length of sensilla styloconica are independent from proboscis length. A unique proboscis morphology was found in the honey‐feeding species Acherontia atropos . Here, the distinctly pointed apex displays a large subterminal opening of the food canal, and thus characterizes a novel type of piercing proboscis in Lepidoptera. In the probably nonfeeding species, the rudimentary galeae are not interlocked and the apex lacks sensilla styloconica; galeal muscles, however, are present. All studied species demonstrate an identical anatomy of the stipes, and suction pump, regardless of proboscis length and diet. Even supposedly nonfeeding Sphingidae possess all organs of the feeding apparatus, suggesting that their proboscis rudiments might still be functional. The morphometric analyses indicate significant positive correlations between galea lumen volume and stipes muscle volume as well as the volume of the food canal and the muscular volume of the suction pump. Size correlations of these functionally connected organs reflect morphological fine‐tuning in the evolution of proboscis length and function. Abstract : The morphology of the proboscis and associated feeding organs was studied in several nectar‐feeding hawk moths, as well as a specialized honey‐feeder and two supposedly nonfeeding species. The proboscis of nectar‐feeding Sphingidae displays uniformous tip morphology. A novel piercing proboscis is described in a honey‐feeding hawk moth. The nonfeeding species have rudimentary but functional proboscises. Size correlations of functionally connected organs reflect morphological fine‐tuning in the evolution of proboscis length and function.